Mitigating and adapting to climate change through silvopasture - Arango, Jacobo; Ramírez Villegas, Julián Armando; Rosenstock, Todd S. (2023)
Livestock production is at the center of adaptation to and mitigation of climate change. It also impacts the Sustainable Development Goals (SDGs). A transition is thus needed for livestock systems to become more sustainable and climate resilient, with clear impacts on the SDGs. This presentation provides an overview of investment priorities for climate resilient and low emissions livestock systems. It also dives deep into trees and agroforestry (silvopasture) as one solution that can help address climate change across the world.